(untitled) (PANGEEA, 2025)
The subject oversees geomatics’s general domain, especially GIS, for establishing some ways of offering accuracy in reaching some sort of superior precision using a strong plannification of Geospatial data base. In this way, we will try to put in work a special analysys exercise which would be built on vector data with real topology. Our work speaks not only to GIS experts, but to those who are working in emergency services: ISU, Police Departments.